A comprehensive tractography study of patients with bipolar disorder and their unaffected siblings. Issue 10 (16th May 2016) - Sprooten, Emma; Barrett, Jennifer; McKay, D Reese; Knowles, Emma E; Mathias, Samuel R; Winkler, Anderson M; Brumbaugh, Margaret S; Landau, Stefanie; Cyr, Lindsay; Kochunov, Peter; Glahn, David C
Abstract: Background: Diffusion tensor imaging studies show reductions in fractional anisotropy (FA) in individuals with bipolar disorder and their unaffected siblings. However, the use of various analysis methods is an important source of between‐study heterogeneity. Using tract‐based spatial statistics, we previously demonstrated widespread FA reductions in patients and unaffected relatives. To better interpret the neuroanatomical pattern of this previous finding and to assess the influence of methodological heterogeneity, we here applied tractography to the same sample. Methods: Diffusion‐weighted images were acquired for 96 patients, 69 unaffected siblings and 56 controls. We applied TRACULA, an extension of a global probabilistic tractography algorithm, to automatically segment 18 major fiber tracts. Average FA within each tract and at each cross‐section along each tract was compared between groups. Results: Patients had reduced FA compared to healthy controls and their unaffected siblings in general, and in particular in the parietal part of the superior longitudinal fasciculus. In unaffected siblings, FA was nominally reduced compared to controls in the corpus callosum. Point‐wise analyses indicated that similar effects were present along extended sections, but with variable effect sizes. Current symptom severity negatively correlated with FA in several fronto‐limbic association tracts. Conclusions: The differential sensitivity of analysis techniques likely explains between‐study heterogeneity in anatomical localization of FA reductions. The present tractography analysis confirms the presence of overall FA reductions in patients with bipolar disorder, which are most pronounced in the superior longitudinal fasciculus. Unaffected siblings may display similar, albeit more subtle and anatomically restricted FA reductions. Hum Brain Mapp 37:3474–3485, 2016 . ©2016 Wiley Periodicals, Inc.